2021
DOI: 10.1111/epi.17124
|View full text |Cite
|
Sign up to set email alerts
|

Surgical evaluation in children <3 years of age with drug‐resistant epilepsy: Patient characteristics, diagnostic utilization, and potential for treatment delays

Abstract: Objective: Drug-resistant epilepsy (DRE) occurs at higher rates in children <3 years old. Epilepsy surgery is effective, but rarely utilized in young children despite developmental benefits of early seizure freedom. The present study aims to identify unique patient characteristics and evaluation strategies in children <3 years old who undergo epilepsy surgery evaluation as a means to assess contributors and potential solutions to health care disparities in this group. Methods:The Pediatric Epilepsy Research Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 29 publications
2
29
0
4
Order By: Relevance
“…A recent study (published subsequent to our search dates) reported of 34 children <3 undergoing epilepsy surgery since 2018, 59% were Engel I outcome at median follow-up of 21.9 months. 37 …”
Section: Discussionmentioning
confidence: 99%
“…A recent study (published subsequent to our search dates) reported of 34 children <3 undergoing epilepsy surgery since 2018, 59% were Engel I outcome at median follow-up of 21.9 months. 37 …”
Section: Discussionmentioning
confidence: 99%
“…25 This "surgical treatment gap" has been steadily improving in the United States pediatric population but epilepsy surgery still remains underutilized. 13,26,27 The underutilization of pediatric epilepsy surgery is multifactorial and includes racial, ethnic, socioeconomic, and medical disparities. Although safe, effective, and recommended for all patients with DRE, there is a misconception amongst patients and health care providers that surgery remains a "last resort" and perceived as being experimental, ineffective, and high risk.…”
Section: Review Article 29mentioning
confidence: 99%
“…25 This “surgical treatment gap” has been steadily improving in the United States pediatric population but epilepsy surgery still remains underutilized. 13 26 27…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the use of multiple antiseizure medications was also negatively associated with longitudinal CVI outcome, and suggests that Practically, it is important for the vision care provider to consider the number of seizure medications and whether if it may be affecting the child's performance during a CVI vision assessment. This would importantly pair up with the increasing tendency toward early aggressive seizure/epilepsy management among neurologists, including offering earlier curative or palliative epilepsy surgery options and few medication trials (Prideaux et al, 2018;Roth et al, 2021;Perry et al, 2022).…”
Section: Epilepsymentioning
confidence: 99%